“I Thought about It and I May Follow What You Said”: Three Studies Examining the Effects of Elaboration and Source Credibility on Risk Behavior Intentions (Journal of International Crisis and Risk Communication Research, 2022)
The induction of cognitive elaboration on information concerning risks may facilitate compliance with messages encouraging audiences to mitigate against risks. Nevertheless, cognitive elaboration and its relationship with other key variables in risk information processing have been largely understudied. Revisiting data from three experiments, this study examined how cognitive elaboration influences behavioral intentions associated with a risk, and the relationship between cognitive elaboration and behavioral intentions, as mediated by perceptions of source credibility. Results consistently found that cognitive elaboration directly predicted increases in both source credibility perceptions and behavioral intentions, along with an indirect effect of cognitive elaboration on behavioral intentions through credibility. Together, the comparative analyses suggest that cognitive elaboration may be a robust factor to aid risk information processing and can be examined in different risk contexts. Practical and theoretical implications, future directions, and limitations are discussed.